Supersymmetric quantum mechanics and the equivalent classical transformation - Agostinho Neto, A. [UNESP]; Drigo Filho, Elso [UNESP] (World Scientific Publishing, 1997)
In the usual supersymmetric quantum mechanics, the supercharges change the eigenfunction from the bosonic to fermionic sector and conversely. The classical correspondent of this transformation is shown to be the addition of a total time derivative of a purely imaginary function to the Lagrangian function of the system.